Slanting talk and its application in prophetic heritage of styles of recitation and demonstration of the significance of what was approved by the languages of Arabs - , Ali Muhsen Badi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This paper is concerned with prophetic hadith that is rooting a famous acoustic phenomenon, slanting particularly in styles of recitation and generally in classical Arabic . The study was divided into three aspects . Firstly it extrapolated the narratives of hadith in its resources, extracted the authentic text, showed its narrators, proved its authenticity, designated the linguistic significance showed the opinions towards its authenticity . Secondly it showed the phonetic significance of the slanting phenomenon in the hadith according to the languages of Arabs . Thirdly it confirmed the relationship between the slanting talk and the talk of revelation of Koran seven characters .